Assessment of power quality terms on energy distribution systems: a case study of Istanbul - Kekezoglu, Bedri; Bozkurt, Altug; Arikan, Oktay; Kocatepe, Celal; Yumurtaci, Recep; Baysal, Mustafa (WYDAWNICTWO SIGMA-NOT SP ZOO, 2012)
Power quality is the most import concern for electrical power distribution systems. The power quality terms have become more harmful in common increasing end-use equipments that have non-linear current-voltage characteristic on energy distribution systems. In this study, power quality terms are investigated on energy distribution systems, Also, as a case study, power quality measurements are shown on Istanbul Electrical Power Distribution System. The measurements conducted under The Power Quality National Project
Keywords: power quality; energy distribution systems; harmonics; flicker; power quality events; Engineering